Efeitos da participação em estudos clínicos randomizados nos desfechos clínicos de receptores de transplante renal - Oliveira, Nagilla Ione de [UNIFESP] (2016)
Objectives: New therapeutic opportunities in kidney transplantation (KT) and improvements in clinical research regulations resulted in an increasing participation of transplant centers in controlled and randomized clinical trials (RCT). This study aimed to evaluate whether the participation of renal transplant recipients (RTR) in an RCT results in clinical outcomes similar or at least not lower in one year of renal transplantation. This information may increase the information for new potential research participants, as well as demonstrate the applicability of randomized clinical trials to the selection of new therapies. Methods: A retrospective observational included data from 1075 KTR during 12 months, stratified into 4 groups: G1 - innovation therapy group (N=319), G2 - internal control therapy group (N=118), G3 - non-participants in RCT which attended selection criteria (N = 319) and G4 - non-participants in RCT which not attended selection criteria (N=319). RCT group were selected from 12 prospective phases II or III RCT, from 1999 to 2010. Non-participants were selected considering transplantation proximity date and original studies criteria. Patients transplanted more than once, block transplantation, identical living donor type (HLA-I) and PRA>50% were excluded. Results: The studied population was young (43±13 years), most male (688, 62%), Caucasians (577, 54%) and KT were mostly with living donor (584, 54%). The composite clinical efficacy outcome, defined as the cumulative survival free of BPAR, death, graft loss or loss to follow-up at 12 months was different between groups (G1:80.3%, G2:78?0%, G3:69?9% and G4:66?1%; p<0,001). Conclusion: KTR participation in RCT significantly influenced the composite clinical efficacy outcome, demonstrating that participation in phases II/III RCT, even those studies when the medication was prematurely interrupted, appears to be a benefit for participants in 12 months of KT. Besides that, the inferior clinical outcomes demonstrated in the G4, draws attention to the difficulty of extrapolating the RCTs results for the population without eligibility criteria, after the new therapies approval.